Malayalam – English Bilingual Bidirectional Dictionary - (:unkn) unknown (My University, 2011)
The fact that literacy and spoken forms are together brought out in these editions, especially in his Malayalam-English dictionary has made the effort even more noteworthy.
Keywords: Malayalam; English